Hydrology and oxygen addition drive nutrients, metals, and methylmercury cycling in a hypereutrophic water supply reservoir - Rodal-Morales, Naivy Dennise; Beutel, Marc; Fuhrmann, Byran; Defeo, Shelby; Hansen, Anne M.; Harmon, Thomas; Brower, Sarah; Pasek, Jeffery (Frontiers in Water, 2024)
Impaired water quality in Mediterranean climate reservoirs is mainly associated with eutrophication and internal nutrient loading. To improve water quality in hypereutrophic Hodges Reservoir, California, United States, a hypolimnetic oxygenation system (HOS), using pure oxygen gas, was implemented in 2020. This study encompasses 3 years of pre-oxygenation data (2017–2019) and 2 years of post-oxygenation data (2020–2021) to understand the cycling of nutrients, metals, and mercury in the reservoir. During the wet year of 2017, mildly reduced conditions lasted until mid-summer in the enlarged reservoir. Nutrients and metals were seen in the hypolimnion including ammonia ( 2 mg-N/L), manganese ( 0.5 mg/L), phosphate ( 0.5 mg-P/L), and sulfide ( 10 mg/L). Production of methylmercury (MeHg), an important bioaccumulative toxin, was favored from April to June with a hypolimnetic accumulation rate of around 200 ng/m2·d. In contrast, the dry year of 2018 exhibited higher hypolimnetic concentrations of ammonia ( 4 mg-N/L), manganese ( 1 mg/L), phosphate (>0.5 mg-P/L), and sulfide (>15 mg/L). The rapid onset of highly reduced conditions in 2018 corresponded with low MeHg hypolimnetic accumulation ( 50 ng/m2·d). It seems that mildly reduced conditions were associated with higher MeHg accumulation, while sulfidic, reduced conditions impaired inorganic mercury bioavailability for MeHg production and/or promoted microbial demethylation. Sulfide also appeared to act as a sink for iron via FeS precipitation, and potentially for manganese via MnS precipitation or manganese coprecipitation with FeS. Mass flux estimates for 2017–2019 indicate that much of the nutrients that accumulated in the hypolimnion moved via turbulent diffusion into the epilimnion at loading rates far exceeding thresholds predicting eutrophic conditions. After oxygenation in 2020–2021, the reservoir water column was highly oxidized but showed a lack of thermal stratification, suggesting reservoir operations in combination with HOS implementation inadvertently mixed the water column in this relatively shallow reservoir. Post-oxygenation, concentrations of ammonia, phosphate, manganese, and mercury in bottom waters all decreased, likely in response to oxidized conditions. Oxygenated bottom waters exhibited elevated nitrate, a byproduct of ammonia nitrification, and iron, a byproduct of FeS oxidation, indicating a lake-wide response to oxygenation.